Perennial forages influence mineral and protein concentrations in annual wheat cropping systems. Issue 3 (5th April 2021) - Clemensen, Andrea K.; Grusak, Michael A.; Duke, Sara E.; Hendrickson, John R.; Franco, José G.; Archer, David W.; Roemmich, James N.; Liebig, Mark A.
Abstract: Agricultural land management may influence crop nutritional quality. However, few studies have explored potential connections between crop quality with different land management strategies. We analyzed mineral and crude protein concentrations in spring wheat grain ( Triticum aestivum L.) samples from a study in Mandan, ND conducted from 2006 to 2014. The study introduced a perennial forage phase into an annual spring wheat cropping system, in three to four replicates, and previously found yield benefits and enhanced soil parameters in the perennial forage treatments. We determined whether integrating a perennial forage phase into continuous wheat would also affect crop nutritional quality by measuring wheat grain mineral and protein concentrations. Crude protein concentration was greater ( p  < .05) when wheat followed alfalfa ( Medicago sativa L.) and increased linearly after 2–5 yr of established alfalfa. We observed comparable wheat grain crude protein and mineral concentrations between continuous annually fertilized wheat and unfertilized wheat following perennial forages. Negative correlations ( p  < .001) were observed between wheat grain yield and crude protein, potassium (K), magnesium (Mg), nickel (Ni), phosphorus (P), sulfur (S), and zinc (Zn) concentrations. Discriminate multivariate analyses showed, with 96% predictive accuracy, that differences in crude protein and mineral concentration were largely driven by year of wheat harvest. Differences between harvest years were likely due to timely precipitation at critical Growth Stage 3, during spikelet development. Study outcomes highlighted the important role of perennial forages and environmental factors to influence protein and mineral concentration in spring wheat grain. Core Ideas:  Perennial forages benefit annual cropping systems.  Wheat grain samples were analyzed for mineral and protein concentration.  Protein was greater when wheat followed alfalfa versus intermediate wheatgrass.  Grain quality was similar between annual cropping and wheat following perennials.  Grain mineral and protein concentrations were influenced by environmental factors.